2021
DOI: 10.3390/ani11010162
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Age and Reproductive Performance of Wild-Born and Escaped Mink (Neovison vison) Caught in the Wild in Denmark

Abstract: The feral mink population in Denmark consists of two groups of animals: mink born in the wild and mink that have recently escaped from farms. The aims of this study were to: (1) estimate the reproductive performance and mortality of the Danish mink born in the wild (wild-born) and mink escaped from farms (captive-born); (2) discuss the likelihood of a self-sustaining population of wild-born mink in Denmark; and (3) model the relationship between the pulp cavity width and the age of mink. During 2018, 247 wild … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 23 publications
0
11
2
Order By: Relevance
“…Thus, it is included in the Spanish Catalogue of Exotic Invasive Species through Royal decree 630/2013 ( , access on 24 April 2021), and is subject to eradication through trapping and culling [ 32 ]. Feral American mink populations, founded by farm-escaped animals living in the wild, have proven self-sustaining without the need for an additional influx of escaped individuals [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is included in the Spanish Catalogue of Exotic Invasive Species through Royal decree 630/2013 ( , access on 24 April 2021), and is subject to eradication through trapping and culling [ 32 ]. Feral American mink populations, founded by farm-escaped animals living in the wild, have proven self-sustaining without the need for an additional influx of escaped individuals [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Necropsy data collected include sex, body length (from tip of nose to start of tail, tail length (start of tail to last vertebra), and fur colour. A recent study has shown that captive-born mink older than 4 months can be separated from wild-born mink using body length, and mink in this study were divided accordingly [ 1 ]. Males with a body length below 43 cm and females with a body length below 39 cm were considered to be wild born following the method used in former studies [ 1 ].…”
Section: Methodsmentioning
confidence: 99%
“…All feral mink in Denmark are American mink ( Neogale vison ) that have escaped from fur farms. The feral mink population in Denmark consists of two subpopulations of mink; wild-born and captive-born mink [ 1 ]. The number of captive-born mink caught by trappers shows a substantial annual supplementation of farmed mink into the feral population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is included in the Spanish Catalogue of Exotic Invasive Species through Royal decree 630/2013 (available at https://www.boe.es/eli/es/rd/2013/08/02/630 ) and subject to eradication through trapping and culling [31]. Wild born mink populations, founded by farm-escaped animals, have proved to be self-sustaining without a continuous influx of captive-born escaped individuals [32].…”
Section: Introductionmentioning
confidence: 99%